The Influence of Electronic Word of Mouth (EWOM) in TikTok Social Media on Purchase Interest of Haircare Products - Nurhandayani, Bernadeta Maria Anie; Sumarto, Agus Herta; Rachbini, Didik J (Indonesian Journal of Business Analytics, 2024)
Online communication has a rapid growth rate through social media, websites, blogs and other media. The increasing popularity of electronic word-of-mouth communication is having a significant impact on consumer behavior. The presence of social media has also changed the way of marketing, from traditional marketing to digital marketing. This study aims to determine the Influence of Electronic Word of Mouth (EWOM) in TikTok Social media on Purchase Interest of Hair Care Products. The research uses a quantitative, causal descriptive approach. The samples used were purposive and accidental sampling with 101 respondents. The research analysis method uses the Partial Least Square (PLS) method based on the Structural Equation Model (SEM) technique. The research findings indicate that Information Adoption and Information Usefulness of eWOM on TikTok have a positive influence on the Purchase Intention of hair care products. Other factors such as Quality, Quantity, Credibility, Information task-fit, Need, and Attitude toward Information also influence the Usefulness of eWOM Information on the TikTok social media platform.